Influence of 17β-estradiol treatment on the expression of NF-κB in complete hydatidiform mole culture (Faculty of Medicine Universitas Indonesia, 2013)
Background: Genetic evidence has established a role of nuclear factor kappa B (NF-κB ) signaling in oncogenesis. However, activity of NF-κB in complete hydatidiform mole (CHM) cell culture under 17Î²-estradiol (E2) treatment is not yet known. Recently, a positive cross-talk between estrogen receptor (ER) and NF-κB to promote survival and progress of cancer cells to a more aggressive phenotype was established. In the present study, we examined the influence of E2 treatment on the NF-κB expression in CHMâs culture. Methods: This experimental study measured the expression of NF-κB in CHM culture treated with E2: 10, 100, 300, 600, and 1000 pg/mL and without E2. Imunohistochemistry staining was used to assess the expression of NF-κB. Microphotographs were taken using 400x magnification. Adobe photoshop CS2 was used to assess the NF-κB expression in cell nucleus. The lower the color intensity of cell RGBbv, is the higher the expression of NF-κB in cells. ANOVA test was performed to compare the expression of NF-κB. Results: NF-κB expression as indicated by color intensity in control group was 114.84 ± 9.02. NF-κB expression in E2 treatment groups were respectively: E2 10 pg/mL: 106.30 ± 13.95; E2 100 pg/mL: 82.47 ± 4.72; E2 300 pg/mL: 82.24 ± 2.67; E2 600 pg/mL: 69.05 ± 6.47; E2 1000 pg/mL: 68.49 ± 2.37. There was progressive decline in color intensity of cells with E2 treatment indicating the increase expression of NF-κB. Significant differences with the control group occurred in doses of E2 100, 300, 600, dan 1000 pg/mL. Conclusion: Treatment of CHM trophoblast culture with escalating doses of E2 was associated with the increase of NF-κB expression in a dose dependent manner. (Med J Indones. 2013;22:197-201. doi: 10.13181/mji.v22i4.599)